2011
DOI: 10.1111/j.1471-4159.2011.07486.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase‐activating polypeptide (PACAP) stimulates the expression and the release of tissue plasminogen activator (tPA) in neuronal cells: involvement of tPA in the neuroprotective effect of PACAP

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) and tissue plasminogen activator (tPA) play important roles in neuronal migration and survival. However, a direct link between the neurotrophic effects of PACAP and tPA has never been investigated. In this study, we show that, in PC12 cells, PACAP induced a 9.85-fold increase in tPA gene expression through activation of the protein kinase A-and protein kinase C-dependent signaling pathways. In immature cerebellar granule neurons (CGN), PACAP stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Cell Motility Measurement-CGN motility was measured using the microexplant technique as previously described (24). Briefly, P7 or P8 rat cerebella were cut into 50 to 100 m pieces and placed in Costar 24-well culture plates double coated with poly-D-lysine (12.5 g/ml, BD Bioscience) and laminin (20 g/ml, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Motility Measurement-CGN motility was measured using the microexplant technique as previously described (24). Briefly, P7 or P8 rat cerebella were cut into 50 to 100 m pieces and placed in Costar 24-well culture plates double coated with poly-D-lysine (12.5 g/ml, BD Bioscience) and laminin (20 g/ml, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the number of biological functions already described for PACAP and VIP, new interesting and emerging role for both peptides are still arising. Indeed, Raoult and coworkers, (2011) [ 35 ] have recently demonstrated that PACAP is a potent inducer of tPA expression in both tumoral and normal neuronal cells, suggesting a novel mechanism of action for the peptide in nerve repair after injury. Nonetheless, Schwann cells also release PAs to aid nerve regeneration, but whether or not PACAP contributes to this process is still unknown, nor are the signaling pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, PC12 cells were plated on glass bottom dishes (MatTek Corporation, MA, USA) for two‐photon microscopy (SP8) or on 24‐well plates (Costar, Illkirch, France) for wide‐field microscopy (CD7) and cultured in a humidified incubator at 37 °C in an atmosphere of 5 % CO 2 . Cells were grown in Dulbecco's modified Eagle's medium (DMEM) (Thermo Fisher Scientific, Illkirch, France) supplemented with 7 % heat‐inactivated fetal bovine serum (Sigma–Aldrich), 7 % horse serum (Lonza Bioscience, Walkersville, MD, USA), 2.5 % HEPES (4‐(2‐hydroxyethyl)‐1‐piperazine ethanesulfonic acid) (Thermo Fisher Scientific), 1 % glutamine (Thermo Fisher Scientific), 100 units/mL penicillin and 100 μg mL −1 streptomycin (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%